Scanning resources to build an international nursing knowledge network - Margareth Santos Zanchetta; Suzanne Fredericks; Kateryna Metersky; Geraldine Martorella; Pammla Petrucka; Laurie Clune; Kelly Graziani Giacchero Vedana; Cristina Rosa Soares Lavareda Baixinho; Cristianne Maria Famer Rocha; Sara Campagna; Sally Zhang He; Márcia Teles de Oliveira Gouveia; et al. (Elsevier, 2024)
This paper reports the gathered information from an international environmental scan of university-baseline information for the creation of a Nursing Knowledge Network. An online environment scan of organizational context (February to October 2021) explored the identification of research areas, existing resources, expected benefits, innovations in teaching research, barriers to knowledge dissemination, and prospective contributions of the Network. Target informants were 200 nursing faculty affiliated with 63 universities located in 13 countries, as well as nursing networks in the Ibero-American context. One informant per university was asked to respond to the questionnaire. The participation rate was nearly 70% (42/63). The informants' universities per country included Brazil (n = 21), Canada (n = 4), Portugal and Spain (n = 3 each), Colombia, Mexico, Peru and USA (n = 2 each), Chile, Italy and Paraguay (n = 1 each). Nursing faculty provided rich information and shared knowledge confirming a strong commitment to global co-creation of innovations and research partnership capacities through collaboration, cooperation, and knowledge exchange among nursing higher education institutions. Seldom researched areas are a potential focus for the Network to generate appropriate evidence to inform local scientific practices. The gathered information will inform further review of nursing and governmental policies and programs related to the application and dissemination of nursing evidence across local, regional, and global levels.